1974
DOI: 10.1111/j.1365-3083.1974.tb01280.x
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Two Distinct Groups of Human IgM and IgA Based on Different Binding to Staphylococci

Abstract: Labeled monoclonal IgM was bound to the Cowan I strain of Staphylococcus aureus in the absence of anti‐IgM antibody This binding was inhibited by 11 of 33 monoclonal IgM proteins; 22 failed to inhibit Agammaglobulinemic serum alto failed to inhibit High concentrations of IgG inhibited the binding of IgM Se to staphylococci, but IgG and IgM probably react with different receptors on tin bacterial surface. Polyclonal IgM from all of 17 individuals tested inhibited the binding of IgM Se to staphylococci, which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

1975
1975
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(43 citation statements)
references
References 24 publications
2
41
0
Order By: Relevance
“…IgM and IgA present in NHS would be expected to precipitate in 5% PEG and some purified preparations of IgM and IgA have been reported to bind to StaphA (10,11). Assay of sera from patients with paraproteinemias (Table I) revealed that some IgA and IgM paraproteins were retained on the StaphA during the procedure, but they did not influence the detection of Agg-IgG using the IgG-specific reagent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…IgM and IgA present in NHS would be expected to precipitate in 5% PEG and some purified preparations of IgM and IgA have been reported to bind to StaphA (10,11). Assay of sera from patients with paraproteinemias (Table I) revealed that some IgA and IgM paraproteins were retained on the StaphA during the procedure, but they did not influence the detection of Agg-IgG using the IgG-specific reagent.…”
Section: Resultsmentioning
confidence: 99%
“…Monomeric IgG (Mon-IgG) and Agg-IgG preparations were adjusted to the desired concentration and sufficient radiolabeled preparations were added such that 100 ,ul contained 5,000-10,000 cpm. The binding studies were performed in duplicate 10 the antisera to reduce the net specific activity by four-to fivefold. This mixture was then diluted 1:4 in PBS-Az containing 5 mg/ml rabbit IgG for use in the SBA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…aureus produces an array of potential virulence factors, including protein A (1,17), a 42-kDa bacterial cell wall component expressed by most strains of S. aureus (6,7). Protein A binds both the Fc␥ region of immunoglobulins (Ig) (6,20,24) and the Fab portion of Ig belonging to the VH3ϩ gene family (13,19,20,24,35). Previous reports have indicated that the binding of protein A to Ig contributes to its mitogenic activity (35), enhances natural killing activity against lymphoid tumor cell lines (28), and induces Ig secretion by human B cells (34).…”
mentioning
confidence: 99%
“…In addition to IgG, protein A also inter acts with human polyclonal IgE [9] and hu man monoclonal IgA and IgM [5]. It was recently demonstrated that the IgE-protein A interaction is mediated by structures lo-cated in the F(ab')2 but not in the Fc" frag ment of IgE [8], Fluman polyclonal IgG is a potent inhibitor of the alternative IgE-protein A interaction [8,9], but its inhibitory effect is exclusively expressed by the F(ab')2y fragment and not by the Fey frag ment [8], A comparison of the mechanisms of interaction between protein A on the one hand and human monoclonal IgG, IgA, and IgM on the other revealed that the alterna tive F(ab')2£ equivalent protein A reactivity is expressed in all three immunoglobulin classes, but to qualitatively varying degrees [7], whereas only IgG proteins express the classical Fcy-protein A reactivity [7].…”
Section: Introductionmentioning
confidence: 99%